Insight into the Role of Ligands in the Yellow Luminescence of Zinc Oxide Nanocrystals. Issue 13 (26th February 2016) - Spataro, Gregory; Dazzazi, Anass; Fortuny, Samantha; Champouret, Yohan; Coppel, Yannick; Rubio‐Garcia, Javier; Bouhaouss, Ahmed; Gauffre, Fabienne; Kahn, Myrtil L.
Abstract: The influence of the composition of the ligand shell on the yellow emission of ZnO nanocrystals (NCs) is reported. The ligand shell was modified either by a change of solvent or by the exchange of the primary alkylamine ligand with an alkylthiol ligand. The changes of the composition of the ligand shell were analyzed by NMR spectroscopy and isothermal titration calorimetry (ITC) and were related to the variation of the visible emission of the ZnO NCs. We demonstrate that the emission wavelength of ZnO is not affected by the medium or the type of ligand at the surface of the NCs; this suggests that the nature of the emitting site is not altered by the environment. However, the quantum yield of this emission is strongly dependent on the composition of the ligand shell, and this implies that the number of emitting sites or their lifetime is varied. This study highlights the possible modification of the optical properties of ZnO NCs through the modification of the surface with organic molecules and paves the way to the application of these ZnO NCs for optical sensors. Abstract : This study highlights the possible modification of the optical properties of ZnO nanocrystals through the modification of the surface state with organic molecules.